Unraveling Adipocytes and Cancer Links: Is There a Role for Senescence? - Wu, Qi; Li, Bei; Sun, Si; Sun, Shengrong (Frontiers in Cell and Developmental Biology, 2020)
Senescence is characterized by a permanent cell cycle arrest that is elicited in response to different stresses. In addition, senescent cells undergo multiple other phenotypic alterations, such as autophagy modulation, metabolic reprogramming, and the senescence-associated secretory phenotype (SASP). These senescence-related and inflammatory effects prevail within tumors and are strongly controlled by cancer properties, and inflammatory mediators further maintain and propagate the senescence process to adjacent cells. It is important to consider these detrimental effects that may drive tumorigenesis or cancer relapse. Importantly, cancer-associated adipocytes (CAAs) are one of the primary stromal cells in various tumor microenvironments and favor tumor progression by releasing various factors that can mediate local and systemic effects. However, it remains unclear whether CAAs possess senescent features. In this review, we discuss the complex relationship between senescence and CAAs and highlight important considerations for therapeutics.